Garden footprint area and water use of gated communities in South Africa - Du Plessis, Jacques L.; Knox, Ashley J.; Jacobs, Heinz E. (Water SA, 2020)
Gated community homes in South Africa are popular amongst property buyers in urban environments such as cities and metropoles due to the increased security and lifestyle improvements offered. Garden design and layout requirements are prescribed in architectural guidelines compiled by the homeowners associations of these communities. Garden footprint area in gated community homes is of importance to researchers and planners, because of the influence on water use. This study used a quantitative approach to evaluate the spatial data of garden footprint area as a percentage of total plot area for 1 813 gated community homes in different regions of South Africa. The research reviewed how garden footprint area is prescribed and how it is applied in gated community homes. The impact of garden footprint area on water use was also analysed. The results were compared to relevant information lifted from specific architectural design guidelines developed for each gated community. Data from 11 gated communities were analysed and the average garden footprint area was found to be 36% of the total plot area. Gated community homes with a garden area smaller than 100 m2 were found to have limited influence on monthly water consumption, while the water use of gated community homes with a larger garden footprint area increased proportionally with garden footprint area. The seasonal fluctuation of water use is illustrative of garden irrigation and other outdoor water use. The results provided useful input for incorporation in outdoor water use modelling of gated community homes.